Efektivitas Kepemimpinan Transformasional dalam Penerapan Kurikulum Berbasis Nilai KeIslaman di Tingkat Sekolah Dasar - Khusyairi Ahmad Hasibuan; Muhammad Hasbie Ashshiddiqi (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Principal leadership is a crucial factor in determining the successful implementation of curricula, including Islamic value-based curricula at the primary school level. This study aims to examine the effectiveness of transformational leadership in implementing Islamic value-based curricula using a literature review approach. Employing a qualitative method—specifically library research—the study analyzes various relevant scholarly articles, academic books, policy documents, and prior research findings. Data were collected via documentation techniques from sources found in databases such as Google Scholar, ScienceDirect, and Garuda, and subsequently analyzed using content analysis involving data condensation, presentation, interpretation, synthesis, and conclusion formulation. The results indicate that transformational leadership plays a significant role in enhancing the effectiveness of Islamic value-based curriculum implementation through a school development vision centered on Islamic values, teacher empowerment, the cultivation of a religious school culture, continuous academic supervision, and strengthened collaboration with parents and the community. Successful implementation is also influenced by the principal's commitment, teacher competence, a conducive organizational culture, and the availability of facilities and infrastructure. Meanwhile, challenges requiring attention include disparities in teacher competence, resistance to change, time constraints, and suboptimal synergy between the school and families. This study affirms that transformational leadership is an effective approach for supporting the implementation of Islamic value-based curricula, fostering an Islamic school culture, improving the quality of instruction, and strengthening the development of students' religious character at the primary school level.